Pengaruh Upah Minimum Provinsi Terhadap Investasi Di Indonesia - Robby Alexander Sirait (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2020)
This research empirically analyzes the effect of the provincial minimum wage on investment in Indonesia. The data were collected from 32 provinces between 2011 and 2019. To analyze cross-province panel data, we used the fixed effect model (FEM). The findings showed a negative relationship between provincial minimum wage and investment, and statistically significant. Another finding is human capital as measured by the level of education, health, and purchasing power of the population has a positive influence on investment and is statistically significant. And finally, we provide a few recommendations that policymakers may adopt in reducing the impact of provincial minimum wage increases on investment.